Giant cell lesions of the jaws. Issue 5 (May 2022) - Walsh, Hannah; Crane, Hannah; Hunter, Keith D.
Abstract: Giant cell rich lesions are frequently encountered in the head and neck region, particularly within the jaw bones. Giant cell rich lesions often require a combination of the clinical presenting features, radiology, and histology to be taken into account before a definitive diagnosis can be achieved. Within this article we aim to highlight the key multinucleated giant cell lesions that show a predilection for the head and neck region, discussing the clinical presentation, radiographic appearance, histological findings, differential diagnosis and treatment options for such lesions.